Study to compare teaching science in some elementary grades using programmed method or the traditional, with a study of the trends of the pupils towards the programmed teaching - Mohammed Reda ElBogdady (Journal of Islamic Studies, 1977)
This research was conducted in a school at Arab republic of Egypt, on a sample of 330 students at grade four and five. Three groups were assigned, two of them from grade four, one of them was experimental and the other was control group. The third group was experimental group. The two experimental groups studied the subject of Microbiology using the programmed method, in order to the control group studied the same subject using the traditional method.